Toward Smart Environment and Forest City Success: Embracing Sustainable Urban Solutions - Listianingsih, Widya; Susanto, Tony (Indonesian Journal on Computing (Indo-JC), 2023)
Solutions to design a more sustainable environment are increasingly urgent in the face of the impacts of climate change and rapid urbanization. In this context, success factors in smart environments and forest cities become essential to accelerate the transformation to a more sustainable environment. This study aims to provide a deeper understanding of the success factors in adopting a smart environment and sustainable forest city from the management aspects of environmental protection, including water, soil, air, waste management, and renewable energy. This research method involves systematic steps in selecting, collecting, and analyzing relevant literature. This research revealed several consistent success factors in the literature and several good practices that can be applied in developing smart environments and forest cities. In conclusion, this research better explains relevant success factors and good practices in creating smart environments and forest cities. It highlights the need for broader and more in-depth research to support efforts to achieve sustainability goals in smart environments and forest cities.